Potential antimicrobial properties of streptomyces isolated from Sammuk Mountain soil, Chonburi Province, Thailand - Paranee Sripreechasak; Anan Athipornchai (Wolters Kluwer Medknow Publications, 2019)
An infection of pathogenic microorganisms can create a big problem for human health. This has triggered the need for discovery and development of antibiotic drugs with altered modes of action. Approximately 45% of antibiotic drugs are derived from Streptomyces, which are the most commonly isolated actinomycete genera. The present investigation aimed to search for and study antimicrobial-producing actinomycetes isolated from soil samples from Sammuk Mountain, Chonburi province, Thailand. A total of 50 isolates from six soil samples were obtained and their actinomycetes were better isolated using humic acid-vitamin agar medium (64.0%) than starch casein nitrate agar medium (36.0%). In addition, the secondary metabolites produced from 13 isolates (26.0%) exhibited a broad spectrum of antimicrobial activity against Gram-positive bacteria and yeast. Thus, Sammuk Mountain soil is an important source of antibiotic-producing actinomycetes.